P‐207: Late‐News Poster: Efficient Emitter Aggregation Management Using High‐Entropy Non‐crystallizable Hosts. Issue 1 (30th May 2018) - Chakraborty, Rajarshi; Molaire, Mike F.; Weiss, David S.; Yu, Tianhao; Rothberg, Lewis J.
Abstract : Molecular Glasses Inc. has developed a new class of high‐entropy non‐crystallizable OLED hosts that can be deposited by both vacuum/thermal evaporation and solution‐based processes such as inkjet printing. Benchmark testing demonstrated a 4‐15 times improvement in OLED lifetime using these hosts instead of conventional host 3, 3‐di(9H‐carbazol‐9‐yl) biphenyl (mCBP). Time resolved photoemission spectroscopy on a yellow phosphorescent emitter in a non‐crystallizable host – OLEDIQ TM HT‐1700 vs. standard mCBP host shows that aggregation quenching is higher in mCBP. Triplet‐triplet annihilation (TTA) in these hosts is also explored.